2014
DOI: 10.1038/nrendo.2014.210
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in early life and obesity

Abstract: The intestinal microbiota can influence host metabolism. When given early in life, agents that disrupt microbiota composition and consequently its metabolic activity, can influence body mass of the host by either promoting weight gain or stunting growth, which is consistent with effects of the microbiota on development. In this Perspective, we posit that microbiota disruptions in early-life can have long-lasting effects on body weight in adulthood. Furthermore, we examine the dichotomy between antibiotic-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
333
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(349 citation statements)
references
References 82 publications
(106 reference statements)
11
333
2
3
Order By: Relevance
“…12,33,34 The effects of some medications on the development of obesity have received considerable attention, for example, the effect of antibiotic use during childhood on obesity 35 Use of other drugs is also related to weight gain and obesity, including several classes of antidepressants: SSRIs, SNRIs and TCAs. 36 These antidepressants are also associated with gut microbiota alterations, which could potentially be a mechanisms by which these drugs cause weight gain.…”
Section: Bmi and Lipid Metabolismmentioning
confidence: 99%
“…12,33,34 The effects of some medications on the development of obesity have received considerable attention, for example, the effect of antibiotic use during childhood on obesity 35 Use of other drugs is also related to weight gain and obesity, including several classes of antidepressants: SSRIs, SNRIs and TCAs. 36 These antidepressants are also associated with gut microbiota alterations, which could potentially be a mechanisms by which these drugs cause weight gain.…”
Section: Bmi and Lipid Metabolismmentioning
confidence: 99%
“…There have been a number of documented incidences in which pharmaceutical companies have not been forthcoming with safety information (Lurie and Wolfe 2005). In recent years, long-term antibiotic use, particularly in the young, has been shown to have adverse health outcomes (Cox and Blaser 2015), yet no pharmaceutical company has faced regulatory consequences. The presence of antibiotics and a range of other drugs in drinking water is now widely reported (Cox and Blaser 2015;Khan et al 2016), presumably owing to urinary excretion.…”
Section: Issues Within the Current Regulatory Frameworkmentioning
confidence: 99%
“…In one study, it was found that elimination of Lactobacillus, Allobaculum, Rikenelleceae, and Candidatus arthromitus led to metabolic changes in rats that eventually welcomed the onset of obesity [56]. To further highlight the impact the composition of an individual's intestinal flora can have on the tendency to gain weight, it was discovered that when germ free mice were given fecal transplants from an Broad-Spectrum Antibiotic Abuse and its Connection to Obesity.…”
Section: Gut Composition Differs Between Obese and Lean Individualsmentioning
confidence: 99%